Monitoring trihalomethanes in chlorinated waters using a dispersive liquid–liquid microextraction method with a non-chlorinated organic solvent and gas chromatography–mass spectrometry. Issue 6 (19th March 2017) - Pacheco-Fernández, Idaira; Herrera-Fuentes, Ariadna; Delgado, Bárbara; Pino, Verónica; Ayala, Juan H.; Afonso, Ana M.
ABSTRACT: The environmental monitoring of trihalomethanes (THMs) has been performed by setting up a dispersive liquid–liquid microextraction method in combination with gas chromatography (GC)–mass spectrometry (MS). The optimized method only requires ∼26 µL of decanol as extractant solvent, dissolved in ∼1 mL of acetone (dispersive solvent) for 5 mL of the environmental water containing THMs. The mixture is then subjected to vortex for 1 min and then centrifuged for 2 min at 3500 rpm. The microdroplet containing the extracted THMs is then sampled with a micro-syringe, and injected (1 µL) in the GC–MS. The method is characterized for being fast (3 min for the entire sample preparation step) and environmentally friendly (low amounts of solvents required, being all non-chlorinated), and also for getting average relative recoveries of 90.2–106% in tap waters; relative standard deviation values always lower than 11%; average enrichment factors of 48–49; and detection limits down to 0.7 µg·L-1. Several waters: tap waters, pool waters, and wastewaters were successfully analyzed with the method proposed. Furthermore, the method was used to monitor the formation of THMs in wastewaters when different chlorination parameters, namely temperature and pH, were varied. GRAPHICAL ABSTRACT: